(untitled) (Analysis in Theory and Applications, 2017)
Let T_1 be a singular integral with non-smooth kernel or ± I, let T_2 and T_4 be the linear operators and let T_3=± I. Denote the Toeplitz type operator byT^b=T_1M^bI_α T_2+T_3I_α M^b T_4,where M^bf=bf, and I_α is the fractional integral operator. In this paper, we investigate the boundedness of the operator T^b on the weighted Morrey space when b belongs to the weighted BMO space.